Dreaming up the right career: an exploratory study of the career aspirations of low-income adolescents living in urban São Paulo - Zakzouk, Mohamed (2015)
In Brazil, low-income youth is prone to unemployment, which is particularly problematic in an emerging economy where income inequality is relatively high, and where future socioeconomic development may depend on the growth and stability of an already vulnerable middle class. Youth unemployment, especially in urban cities, is also associated with high incidents of violence, illegal behaviour, widening inequality and sociopolitical instability. The present study complements existing efforts to advance the employment prospects of Brazilian youth, by exploring the career aspirations of 25 late adolescents living in low-income communities in urban Sao Paulo. The research was conducted by means of focus groups, over the course of four meetings in the Paulistano communities of Vila Albertina, Heliopolis, Vila Prudente and Vila Nova Esperança. The research findings largely echo existing knowledge pertaining to adolescents: they confirm the important role of individual merit, the micro-environment and role models (namely family, peers and local educators) in shaping and enabling (or hindering) the career paths of young adults, and highlight the flexibility and diversity of professional interests during that age. Furthermore, the findings reveal paradoxical attitudes towards low-income communities in Sao Paulo. All participants seemed empowered by elements within their micro-environment, exhibiting sentiments of pride and belonging to their community, yet many seemed troubled by how outsiders stereotype or stigmatize 'favela' dwellers. Overall, the study highlights tendencies that support the case for further investment in the professional development of youth at the base of the economic pyramid. As a potential ecosystem for socioeconomic development, low-income communities can constitute a rich source of not only human capital, but also business opportunities and employment.